A real-world disproportionality analysis of Tenofovir Alafenamide (TAF): Data mining of the FDA adverse event reporting system (FAERS) - Chao Zhang; Jiaqi Wen; Yinghui Li (PLoS ONE, 2025)
Objects Tenofovir Alafenamide (TAF) is a novel antiviral drug approved for the treatment of hepatitis B virus (HBV) infection. Our research objective was to evaluate the safety characteristics of TAF in practical settings by analyzing data from the FDA adverse event reporting system (FAERS) database maintained by the Food and Drug Administration (FDA). Method In our investigation, we examined the uneven distribution of adverse events associated with TAF by employing statistical metrics including the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Gamma-Poisson Shrinker (GPS) to determine their significance. Results Out of the 57692002 case reports in the FAERS database, 1911 reported TAF as a major suspected (PS) adverse events (AEs). A disproportionate analysis identified 43 preferred terms (PTs) related to TAF. It is worth noting that we have observed unexpected significant adverse events, such as cerebral infarction, bone pain, swallowing difficulties, drug resistance, dementia, etc., which are not mentioned in the drug instructions. Conclusion These findings unearth novel neurological, metabolic, and resistance - related risks, thereby necessitating a marked increase in clinical vigilance. The identification of signals related to cerebral infarction and dementia implies potential vascular/metabolic interplay, highlighting the importance of lipid monitoring among long - term tenofovir alafenamide (TAF) users. In response, healthcare providers should prioritize strengthening the monitoring of neurological symptoms and lipid profiles, reevaluating bone health assessment and management protocols especially in high - risk populations, and providing support to enhance patient adherence to mitigate resistance risks. This analysis offers crucial post - marketing evidence, which is instrumental in optimizing the risk - benefit balance of TAF in the long - term management of chronic hepatitis B virus (HBV) infection.